2015
DOI: 10.1111/gbb.12194
|View full text |Cite
|
Sign up to set email alerts
|

Human‐directed social behaviour in dogs shows significant heritability

Abstract: Through domestication and co-evolution with humans, dogs have developed abilities to attract human attention, e.g. in a manner of seeking assistance when faced with a problem solving task. The aims of this study were to investigate within breed variation in human-directed contact seeking in dogs and to estimate its genetic basis. To do this, 498 research beagles, bred and kept under standardized conditions, were tested in an unsolvable problem task. Contact seeking behaviours recorded included both eye contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
85
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 48 publications
6
85
3
Order By: Relevance
“…The distinct behavioral predispositions of individual dog breeds clearly indicate a strong genetic component to dog personality, which is further strengthened by estimates of substantial within-breed genetic variance found for a variety of dog behavioral traits across studies ( e.g. , Wilsson and Sundgren 1997; Saetre et al 2006; Meyer et al 2012; Arvelius et al 2014a; Persson et al 2015). …”
mentioning
confidence: 92%
“…The distinct behavioral predispositions of individual dog breeds clearly indicate a strong genetic component to dog personality, which is further strengthened by estimates of substantial within-breed genetic variance found for a variety of dog behavioral traits across studies ( e.g. , Wilsson and Sundgren 1997; Saetre et al 2006; Meyer et al 2012; Arvelius et al 2014a; Persson et al 2015). …”
mentioning
confidence: 92%
“…In a seminal study comparing wolves and dogs, Miklósi and colleagues found that when confronted with an unexpectedly unsolvable task, 4 month-old pet dogs were more likely to “look back” to their owner and did so sooner and for longer than wolves of the same age raised in a ‘pet-like’ environment3. Since this first study, the propensity to look back in dogs has been shown to differ between breed-groups67 and to have a genetic basis89, providing further circumstantial support for a potential effect of domestication on this behaviour.…”
mentioning
confidence: 99%
“…Moreover, it has recently been shown that mechanism of processing emotional auditory information in the brain is alike in dog and man (Andics et al ). Efficient inter‐specific communication and an at least as strong bonding to humans than to conspecifics seem to be inherited features critical in differentiating the domesticated dog from wolves (Miklosi and Topal , Persson et al , Udell et al , Viranyi et al ). Nevertheless, the questions remain: which pathway of the nervous system could mostly be affected, and do behavioral differences characteristic to breeds or individual dogs reflect variations within this system?…”
mentioning
confidence: 99%